2020
DOI: 10.23917/jiti.v19i1.10231
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Model of Knowledge Sharing in Business Innovation to Improve the Performance of Micro Small and Medium Enterprises

Abstract: Innovation performance can be an important indicator for organizations because it can enhance competitive advantage. In the organizational context, the results of innovation can be drawn by increasing efficiency, productivity, quality, competitive advantage, and market development. Micro, small, and medium entreprises (MSMEs) generally have to face challenges such as limited financial resources, sub-optimal operations, inefficient supply chains, limitations in technology application, and unpreparedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…Then, the effect of explicit knowledge sharing on financial performance was supported and positive too, while for marketing performance, it was supported but the effect was negative.The results of this study indicated that the performance of MSMEs would increased when the application of knowledge sharing went well, this could be seen from the test results which showed that tacit knowledge sharing had a positive and significant effect on marketing performance and explicit knowledge sharing had a positive and significant effect on financial performance. This was in line with the results of previous research done by [6], [7], [10]- [12], which showed that knowledge sharing was able to make a positive contribution to improving organizational business performance. However, it was different from the effect of explicit knowledge sharing on marketing performance which showed a negative and significant influence, which strengthened the results of research [13]- [15] that knowledge sharing had no significant effect on business performance.…”
Section: Resultssupporting
confidence: 92%
“…Then, the effect of explicit knowledge sharing on financial performance was supported and positive too, while for marketing performance, it was supported but the effect was negative.The results of this study indicated that the performance of MSMEs would increased when the application of knowledge sharing went well, this could be seen from the test results which showed that tacit knowledge sharing had a positive and significant effect on marketing performance and explicit knowledge sharing had a positive and significant effect on financial performance. This was in line with the results of previous research done by [6], [7], [10]- [12], which showed that knowledge sharing was able to make a positive contribution to improving organizational business performance. However, it was different from the effect of explicit knowledge sharing on marketing performance which showed a negative and significant influence, which strengthened the results of research [13]- [15] that knowledge sharing had no significant effect on business performance.…”
Section: Resultssupporting
confidence: 92%
“…Through knowledge sharing, employees of an organization mutually discuss their work experience and exchange information and expertise, which ultimately helps them generate new knowledge (Louati & Hadoussa, 2021). Therefore, knowledge sharing is composed of two parts: (1) knowledge donating and (2) knowledge collecting (Putro & Ilmaniati, 2020). Knowledge donating is the interaction between two or more people that relies upon one's desire to transfer their knowledge to others.…”
Section: Social Media Usage and Knowledge Sharingmentioning
confidence: 99%
“…A marketing strategy is a plan to choose and study a target market as well as develop and maintain a marketing mix that may satisfy its customers' needs [6]. In these circumstances, business players are forced to adapt by making certain adjustments, such as selling things online, promoting their products through social media, or developing their website [7] [8].…”
Section: Introductionmentioning
confidence: 99%